2016
DOI: 10.1007/s10734-015-9976-5
|View full text |Cite
|
Sign up to set email alerts
|

Team-taught versus individually taught undergraduate education: a qualitative study of student experiences and preferences

Abstract: Team teaching is becoming more common in undergraduate programmes of study although the relative merits to the more traditional individually taught courses have not been determined for best practice. For this study, 15 final-year undergraduate computer science students were interviewed to gain insight into their learning experiences. A thematic analysis of the interview data identified the perceived advantages and disadvantages of each mode of teaching. The advantages of individually taught courses included: c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 27 publications
0
14
0
1
Order By: Relevance
“…In order to be effective, feedback must be presented within a reasonable timeframe and consequently UoN has a 21 day 'turn around' rule for marks/feedback (Nicol & Macfarlane-Dick, 2006). Although Core Skills is taught via a team teaching approach (Money & Coughlan, 2016), academics found it increasingly difficult to provide feedback on assessment whilst delivering new teaching as the term progressed. The pressures, including class size expansion, that reduce feedback opportunities on assessment such as oral presentations are well known (De Grez, Valcke, & Roozen, 2009;Leger, Glass, Katsiampa, Liu, & Sirichand, 2015;van Ginkel, Gulikers, Biemans, & Mulder, 2016).…”
Section: The Study's Rationalementioning
confidence: 99%
See 1 more Smart Citation
“…In order to be effective, feedback must be presented within a reasonable timeframe and consequently UoN has a 21 day 'turn around' rule for marks/feedback (Nicol & Macfarlane-Dick, 2006). Although Core Skills is taught via a team teaching approach (Money & Coughlan, 2016), academics found it increasingly difficult to provide feedback on assessment whilst delivering new teaching as the term progressed. The pressures, including class size expansion, that reduce feedback opportunities on assessment such as oral presentations are well known (De Grez, Valcke, & Roozen, 2009;Leger, Glass, Katsiampa, Liu, & Sirichand, 2015;van Ginkel, Gulikers, Biemans, & Mulder, 2016).…”
Section: The Study's Rationalementioning
confidence: 99%
“…Participants were told there was no obligation to participate and that they could engage or withdraw without prejudice. Participation was anonymous, and following the approach of Money and Coughlan (2016), participation (or not) would have no impact on grades.…”
Section: Ethicsmentioning
confidence: 99%
“…Las prácticas pedagógicas son procesos vinculados, por una parte, con las habilidades socioafectivas desplegadas en el proceso educacional Significaciones de jóvenes universitarios sobre derechos humanos o de aprendizaje; de ahí, entonces, que los grados de comprensión dependen de prácticas en las cuales, directa o indirectamente, los contenidos disciplinarios se ajustan a los derechos humanos. Sin embargo, a partir de estos hallazgos, se puede concluir que falta agenciar una narrativa que vincule los elementos del contenido sobre derechos humanos a un enfoque acomodado a la comprensión que los estudiantes requieren (Money y Coughlan, 2016).…”
Section: Categoría 1: Las Prácticas Pedagógicas Y Las Significacionesunclassified
“…This happens as faculty with different pedagogical styles work together to help students with various learning needs (Sullivan et al, 2013). In addition, prior work has found that team teaching improves student satisfaction (Sullivan et al, 2013) and exposes students to broad viewpoints on topics, providing a deeper understanding of the content (Benjamin 2000;Hanusch et al, 2009;Money and Coughlan 2016).…”
Section: Team Teachingmentioning
confidence: 99%
“…This happens as faculty with different pedagogical styles work together to help students with various learning needs (Sullivan, Colburn, & Fox, 2013). In addition, prior work has found that team teaching improves student satisfaction (Sullivan et al, 2013) and exposes students to broad viewpoints on topics, providing a deeper understanding of the content (Benjamin, 2000; Hanusch, Obijiofor, & Volcic, 2009; Money & Coughlan, 2016). Furthermore, team teaching within business schools helps professors integrate different functional areas, such as accounting, management, and marketing, in a single course (Heinfeldt & Wolf, 1998).…”
Section: Team Teachingmentioning
confidence: 99%